Determination of perceptions of social workers about the employee health and wellness programme at the Polokwane Municipality of Limpopo Province - Sefala, Mmatholo Constance (My University, 2021)
Background: Employee Health and Wellness Programme is an intervention by government to build and maintain a health promoting workplace. The programme aims to address various health and wellness problems employees‟ face that may negatively impact their performance and productivity. The programme is available for social workers; however, their utilisation is low. It is important to understand how social workers perceive the programme, in order to enhance provision of this programme to them and to promote their general health and wellness. Objectives: The study was aimed at exploring and describing the perceptions of social workers about the Employee Health and Wellness Programme. Methods: A qualitative, exploratory descriptive study was conducted using semi-structured face-to-face interview. The study site was at the selected locations in the Polokwane Municipality. Purposive sampling was used and due to data saturation, 10 participants were interviewed. All the interview sessions were audio recorded, transcribed and analysed using content analysis. Results: The results highlighted positive and negative perceptions about the Employee Health and Wellness Programme among social workers and the Department of Social Development. The positive perceptions include alleviating stress and burnout, reduced sick leaves and increased productivity. The negative perceptions include stigma and confidentiality issues. The results also revealed challenges of accessibility, awareness, promotion and marketing of the programme. These challenges make it difficult for social workers to utilise and benefit from the programme as expected. Conclusions: The Employee Health and Wellness Programme should be well implemented, widely marketed and promoted to all employees within the Department of Social Development.
Thesis (MPH.) -- University of Limpopo, 2021
Keywords: Perceptions; Social workers; Employee Health and Wellness Programme; Content Analysis; Employee health promotion; Social workers -- South Africa -- Limpopo